2018
DOI: 10.1159/000490463
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the <b><i>LEP</i></b> -2548G/A Promoter and Baseline Weight and between <b><i>LEPR</i></b> Gln223Arg and Lys656Asn Variants and Change in BMI <b><i>z</i></b> Scores in Arab Children and Adolescents Treated with Risperidone

Abstract: Data on baseline (antipsychotics-naïve) age, weight, and height, and change in these at 3 subsequent follow-up time points up to 313.6 days (95% CI 303.5–323.7) were collected from 181 risperidone-treated children and adolescents (mean age 12.58 years, SD 4.99, range 2.17–17.7) attending a pediatric neurology clinic in Saudi Arabia. Owing to differences in genotypic distributions in the subsamples, results are reported for the white Arab population (n = 144). Age- and gender-normed body mass index (BMI)-standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(42 reference statements)
1
1
0
1
Order By: Relevance
“…The associations seen with the G allele of the LEPR SNP rs1137101 were observed with both weight gain and weight relatively stable for T1D and T2D groups versus controls. This is in keeping with previous reports about this allele and its relation to BMI in people prescribed sodium valproate [ 32 ] although the GG genotype was associated with less BMI increase over time in that study [ 33 ]…”
Section: Discussionsupporting
confidence: 92%
“…The associations seen with the G allele of the LEPR SNP rs1137101 were observed with both weight gain and weight relatively stable for T1D and T2D groups versus controls. This is in keeping with previous reports about this allele and its relation to BMI in people prescribed sodium valproate [ 32 ] although the GG genotype was associated with less BMI increase over time in that study [ 33 ]…”
Section: Discussionsupporting
confidence: 92%
“…Se ha revisado otro estudio en el que ciertas variantes genéticas se asocian con diferencias en el incremento de índice de masa corporal en niños y adolescentes que comienzan tratamiento con risperidona (32). La variante genética rs1137101 del receptor de leptina (LEPR) está directamente relacionada con el incremento de peso durante el tratamiento con dicho fármaco.…”
Section: Otrosunclassified
“…Analysis of the scientometric PubMed database showed that the most studied association between obesity and type 2 diabetes are the following SNPs of the LEPR gene: rs3790435 [11] and missense mutations rs1137100 [12,13], rs1137101 [14,15], rs1805094 [16], rs8179183 [17], which are located in gene regions encoding functionally significant domains of the LEPR protein.…”
mentioning
confidence: 99%